4y2=36

Divide each term in 4y2=36 by 4.

4y24=364

Cancel the common factor of 4.

Cancel the common factor.

4y24=364

Divide y2 by 1.

y2=364

y2=364

Divide 36 by 4.

y2=9

y2=9

Take the square root of both sides of the equation to eliminate the exponent on the left side.

y=±9

Simplify the right side of the equation.

Rewrite 9 as 32.

y=±32

Pull terms out from under the radical, assuming positive real numbers.

y=±3

y=±3

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

y=3

Next, use the negative value of the ± to find the second solution.

y=-3

The complete solution is the result of both the positive and negative portions of the solution.

y=3,-3

y=3,-3

y=3,-3

Solve using the Square Root Property 4y^2=36